2018
DOI: 10.1111/avj.12704
|View full text |Cite
|
Sign up to set email alerts
|

Review of 20 years of human acute Q fever notifications in Victoria, 1994–2013

Abstract: There has been a reduction in cases of acute Q fever in Victoria over the past 20 years and a changing epidemiology with respect to age, sex and acquisition source. Epidemiological and spatiotemporal analyses suggested a low level of endemic transmission within the state, with multiple foci of increased zoonotic transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…Rather, this pattern could reflect heightened awareness of the disease and its health impacts, or perhaps a shift from primarily acute cases in livestock workers to non‐occupational cases that are more difficult to diagnose due to a lack of obvious exposure pathways. Indeed, the authors of a recent time‐series analysis of Q fever notifications in Victoria, Australia, found evidence for such a pattern and postulated that many mild cases likely remain undiagnosed, leading to a relatively high hospitalization rate for those more severe cases that are confirmed as Q fever (Bond et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, this pattern could reflect heightened awareness of the disease and its health impacts, or perhaps a shift from primarily acute cases in livestock workers to non‐occupational cases that are more difficult to diagnose due to a lack of obvious exposure pathways. Indeed, the authors of a recent time‐series analysis of Q fever notifications in Victoria, Australia, found evidence for such a pattern and postulated that many mild cases likely remain undiagnosed, leading to a relatively high hospitalization rate for those more severe cases that are confirmed as Q fever (Bond et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Q fever is a globally distributed emerging infectious disease caused by the bacterium Coxiella burnetii (Allan‐Blitz, Sakona, Wallace, & Klausner, 2018; Bond, Franklin, Sutton, Stevenson, & Firestone, 2018; Gyuranecz et al., 2014; Van der Hoek et al., 2010). Acute infection with C. burnetii is commonly described as a flu‐like illness with symptoms including high fevers, headaches or pneumonia, as well as atypical symptoms such as hepatitis or myocarditis (Raoult & Marrie, 1995; Sellens et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Increased incidence of local acquisition of human infection may be associated with high prevalence in livestock [32]. Hence, investigation of C. burnetii seroprevalence in sheep from New South Wales and Queensland is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Using risk analysis maps, the authors of our final paper in this issue identified risk areas according to location over time . They show an overall decrease in the numbers of notifications, particularly those associated with abattoirs, and a relative increase in the numbers of women affected.…”
Section: One Healthmentioning
confidence: 99%